ANALISIS KEBUTUHAN TENAGA TEKNIS KEFARMASIAN BERDASARKAN BEBAN KERJA PADA PELAYANAN RESEP DI INSTALASI FARMASI RAWAT JALAN RS ROEMANI MUHAMMADIYAH SEMARANG - Darsono, Dwi Aryaningtyas; Suwarni, Sri; Indrasari, Ferika; Rosita, Dian; Roslianti, Rini (Jurnal Farmasi & Sains Indonesia, 2022)
One indicator of the success of an effective and efficient hospital is the availability of a sufficient number of human resources (HR) with high quality and professionalism in accordance with the functions and duties of each personnel. The Hospital Pharmacy Installation is a unit that plays a major role in supporting hospital operations. The purpose of the study was to determine the ratio of pharmaceutical technical personnel needs based on WISN analysis in the outpatient pharmaceutical installation of Roemani Muhammadiyah Hospital Semarang. This research is included in the type of descriptive qualitative research whose data management uses descriptive quantitative research studies. The method used workload indicators of staffing need (WISN) this method is accurately used to calculate the needs of human resources (HR) based on the real workload. The results showed that the need for pharmaceutical technical personnel at Roemani Muhammadiyah Hospital Semarang was 25 people, the comparison of reality and needs (ratio) of pharmaceutical technical personnel was 0.9, which showed that the number of pharmaceutical technical personnel was not in accordance with the existing workload. Factors underlying the need for pharmaceutical technical personnel in the outpatient installation include many prescriptions that accumulate in crowded hours, the work system is not yet appropriate, the pharmacy layout is not effective efficient, and the number of prescriptions served is not proportional to the current number of pharmaceutical technical personnel.